DAYA DUKUNG FISIK KAWASAN EKOWISATA MANGROVE DI RESORT GRAJAGAN TAMAN NASIONAL ALAS PURWO - , Dwi Ariyanto, SH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Research Carrying Capacity of Mangrove Ecotourism in the Grajagan Resort Alas Purwo National Park in June s. d December 2011. The purpose of this study was to determine the maximum number of visitors that can be received at the location of the Mangrove Resort Ecotourism through the methodology of Grajagan developed by Cifuentes (1992) by taking into account Physical Carrying Capacity (PCC), Real Carrying Capacity (RCC) and Effective Carrying Capacity (ECC). determined to two locations, namely The capacity of carrying in the mangrove ecotourism areal the mangrove ecotourism entrance and line boating in the Segoroanak River. The enormous of the physical carrying capacity (PCC1) at the entrance to the area is the mangrove ecotourism 38.048 visits every day. While the capacity of the physical carrying capacity (PCC2) on boating in the Segoroanak River along the 6 Kilometres from Cungur Block up to Kere Block is 960 boat every day. . The determination of the real carrying capacity (RCC), taking into account the physical carrying capacity (PCC) with various correction factors such as the illumination of the sun (Cf1 = 47,95%), precipitation (Cf2 = 14,69%), the condition of the surface of the lowtide (Cf3 = 19,52%), distrubance of wildlife species of long-tailed Macaques (Macaca fascicularis) registration (Cf4 = 16,44%), disruption of wildlife species of Monitor Lizard (Varanus salvator) registration (Cf5 = 8,22%), distrubance of wildlife migrant bird species (Cf6 = correction factor 65,75%) and temporary closure (Cf7 = 27.12%). So the real carrying capacity (RCC1) on mangrove entrance area of 2.603 ecotourism visits every day and on the boating on the Segoroanak River along the 6 Kilometres from Kere Block up to Cungur Block RCCâ is 66 boat every day . Determination and the Effective Carrying Capacity (ECC) takes into account the value of the real carrying capacity (RCC) with management capacity (MC) and infrastructural capacity (IC). In the area of the entrance of the mangrove ecotourism retrieved MC amounting to 75% and amounted to 720, so IC effective carrying capacity (ECC1) 20,75% of RCC1 (2,603) i.e. 540 visits every day or 197.100 visits every year. While on boating in the Segoroanak River MC of 72,22% and amounted to 44, so IC effective carrying capacity (ECC2) on this line of 48,39% of RCC2 (65), i.e. 32 every day boat excursions or visits of 11.680 every year. Rate of visit ors every year at the mangrove ecotourism Grajagan Resort in 2009 (22.488 / year), 2010 (67.976 / year) and 2011 (56.685 / year) range from 11% to 29% of the value of ECC1 (197.100 / year). However, when the level of visits every day is allowed i.e. ECC1 amounting to 540 visits every day, that exceeded the level of his visit on Saturday and Sunday.